2006
DOI: 10.1007/s00253-005-0265-6
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of sugar cane molasses with/without the presence of lignosulfonate for the production of bacterial cellulose

Abstract: Production of bacterial cellulose (BC) using sugar cane molasses (MO) with/without the presence of lignosulfonate (MOL) as a sole carbon source in a Hestrin-Schramm medium (HS) was investigated. Six strains of Acetobacter xylinum [American Type Culture Collection 10245 and Institute of Fermentation in Osaka (IFO) 13693, 13772, 13773, 14815, and 15237] were screened for their BC production. The yield of the BC among all the strains from both the MO and MOL media was much higher than that from the HS medium. Ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 19 publications
4
49
0
2
Order By: Relevance
“…Thus, it was confirmed that the medium compositions gave some influence on the crystalline phase of the BC. These results agreed with those of Keshk and Sameshima who found that use of molasses resulted in a small decrease in crystallinity index of BC produced by A. xylinum strains [33]. On the other hand, Watanabe et al [34] and Iwata et al [35] reported that BC produced in agitated culture had lower crystallinity index than that in static culture.…”
Section: X-ray Diffractometrysupporting
confidence: 91%
“…Thus, it was confirmed that the medium compositions gave some influence on the crystalline phase of the BC. These results agreed with those of Keshk and Sameshima who found that use of molasses resulted in a small decrease in crystallinity index of BC produced by A. xylinum strains [33]. On the other hand, Watanabe et al [34] and Iwata et al [35] reported that BC produced in agitated culture had lower crystallinity index than that in static culture.…”
Section: X-ray Diffractometrysupporting
confidence: 91%
“…Further as mentioned earlier, there is a tendency to use many different substrates/agricultural byproducts (cane molasses, beet molasses, pineapple skin, cheese whey permeate, high solids potato effluents for the manufacture of nata-de-coco (Keshk and Sameshima 2006). Under such circumstances there is a greater need for standardization of the manufacturing process and for stricter controls/specifications.…”
Section: Resultsmentioning
confidence: 96%
“…Of all, adding appropriate stimulatory factors has received much attention for its simplicity and already observed significant effects on BC production. At present, studies on stimulatory factors mainly focus on ethanol (Naritomi et al 1998a), organic acids (Embuscado et al 1994;Toda et al 1997;Naritomi et al 1998b), Water-Soluble Polysaccharides (Bae et al 2004;Ishida et al 2003), and lignin sulfonate (Keshk and Sameshima 2006). Among them, ethanol has been shown to be a good stimulatory factor for BC production, and the underlying mechanism has also been investigated (Yunoki et al 2004).…”
Section: Introductionmentioning
confidence: 97%